Reconstructing the Paradigm of Corporate Social Responsibility Based on Pancasila and Social Justice - Jejen Hendar (Research Synergy Foundation, 2025)
The implementation of Corporate Social Responsibility (CSR) in Indonesia has long been regulated through formal legal instruments, particularly Article 74 of the Company Law. However, in practice, CSR has often been reduced to a symbolic obligation that serves reputational interests rather than fulfilling its social justice function. This article analyzes the normative foundation of CSR in Indonesia from the perspective of Pancasila, particularly the fifth principle: social justice for all Indonesian people. Using a normative juridical method and a philosophical-ideological approach, the study finds that CSR must be repositioned not merely as a corporate instrument but as an ethical and legal mandate rooted in national ideology. The article argues that CSR must be reconstructed as a distributive justice mechanism that addresses structural inequalities, ensures equitable benefit distribution, and involves affected communities in planning and implementation. The findings recommend strengthening the legal framework of CSR by integrating the substantive values of Pancasila and establishing clear mechanisms for accountability, transparency, and public participation. This reconstruction is necessary to align CSR practices with Indonesia’s constitutional and moral obligations to realize social justice.